Chemical Solution Deposition of BaxSr1-xTiO3 Thin Films for Energy Storage Applications - Federica Benes; Mirela Dragomir; Barbara Malič; Marco Deluca (Proceedings, 2020)
Highly textured Ba0.5Sr0.5TiO3 and Ba0.6Sr0.4TiO3 thin films have been successfully processed using chemical solution deposition (CSD) techniques and annealed at different temperatures to investigate the influence on crystal growth. Microstructure and texture have been evaluated using SEM and XRD techniques. The films showed a homogeneous thickness of ~120 nm and the grain growth seemed to be highly influenced by the annealing temperature. Moreover, by tuning the deposition and annealing conditions, an almost epitaxial growth of Ba0.6Sr0.4TiO3 on the platinized silicon substrate has been achieved. Nevertheless, the samples showed severe cracking due to the strain imposed by the substrate or due to the growing direction.